Phytochemical compounds and the effect of ‘bangunbangun’ leaves (Coleus amboinicus, L.) water extract on phagocytosis activity of neutrophil cell rat (Rattus norvegicus) - Christin Marganingsih Santosa; Triana Hertiani (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2005)
Traditional medicine has been recognized and widely used in Indonesia for healthy care or alternative medication in certain diseases. However, without scientific evidence, traditional medicine of empirical evidence cannot be used for modern health medication. This research was designed to find out the mains compound despite of Bangun-bangun aqueous extract from Kaliurang district using phytochemistry analysis such as Thin Layer Chromatography method and determine the effect on neutrophil cell activities by observing their phagocytosis. The result showed that the main compounds of Bangun-bangun leaves from Kaliurang district are polyphenol, saponin, flavonol glycoside and essential oil. Administration of the extract with the doses of Bangun-bangun leaves treatment 19,0 g/kg bw/oral/day (group A) and 31,5 g/kg bw/oral/day (group B) increased neutrophil cell phagocytosis up to 50% and 60 %, respectively, compared to those of controls which is 10% during 30 days treatment. Neutrophil cell phagocytosis in group B and C capability increase up to 80% (p